Розподіл за флористичними областями ефіроолійних рослин, інтродукованих у Донецькому ботанічному саду НАН України - Gorlachova, Z.S. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
As a result of the analysis on the distribution of 172 essential oil plant species in the floristic areas, perspective areas and provinces have been determined, where the greatest number of the successfully introduced into the Donbas conditions species is located. The analysis has shown that the species growing in the secondary genetic centers were characterized by a high polymorphism and a wide range of adaptation potential. The factors, limiting introduction of the studied species under the conditions of Donbas have been revealed.